2002
DOI: 10.1097/00004703-200204000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Harmful Sleep Habits of 3-Year-Old Children in Japan

Abstract: To examine the sleep habits of 3-year-old children, we questioned guardians during a routine health examination for 3-year-old children at a public health center. According to the 1105 questionnaires analyzed, the proportion of children who fell asleep at 10 p.m. or later was 49.6%. The nocturnal sleep onset time was significantly correlated with the wake-up time in the morning and was significantly negatively correlated with the nocturnal sleep duration. The average daily total sleep duration (nocturnal sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 8 publications
2
38
6
Order By: Relevance
“…Chronic insufficient sleep and sleep loss are common problems in modern industrial societies because annual work hours have become extended and a larger number of people are engaged in shift-work compared with the past (Aldrich 2003). Consistent with these trends in adults, bedtime has become progressively delayed, and sleep duration shortened among adolescents and children in industrial countries (Kohyama et al 2002;Gangwisch et al 2010;Asaoka et al 2010). Studies conducted in a suburban area of Tokyo showed that the proportion of 3-year-old children going to bed at 10 PM or later increased from 22% in 1980 to 50% in 2000 (Okawa and Uchiyama 1998;Kohyama et al 2002).…”
mentioning
confidence: 91%
“…Chronic insufficient sleep and sleep loss are common problems in modern industrial societies because annual work hours have become extended and a larger number of people are engaged in shift-work compared with the past (Aldrich 2003). Consistent with these trends in adults, bedtime has become progressively delayed, and sleep duration shortened among adolescents and children in industrial countries (Kohyama et al 2002;Gangwisch et al 2010;Asaoka et al 2010). Studies conducted in a suburban area of Tokyo showed that the proportion of 3-year-old children going to bed at 10 PM or later increased from 22% in 1980 to 50% in 2000 (Okawa and Uchiyama 1998;Kohyama et al 2002).…”
mentioning
confidence: 91%
“…The nocturnal sleep onset of children has become progressively later in Japan (Kohyama et al 2002). It is considered possible that both late bedtime and shortened sleep duration might have deleterious effects on the development of children.…”
mentioning
confidence: 99%
“…32 Sleep duration at night is determined by the period between bedtime and waking up during which children remain in the bed. 11,21 In the present study, the mean sleep duration at night was 8.3±1.9 hours at all ages (3-12 hrs).…”
Section: Discussionmentioning
confidence: 99%